An Analytical Model for Oblique Cross Section Nanoindentation of Ion‐Irradiated Metallic Alloys Based on Studies of Oxide Dispersion Strengthened Steel MA957. Issue 5 (25th January 2021) - Bhattacharyya, Dhriti; Hurt, Christopher; Xu, Alan; Ionescu, Mihail
Abstract : Herein, oblique cross section (OCS) nanoindentation is used to measure the hardness changes in He 2+ ion‐irradiated oxide dispersion strengthened (ODS) steel MA957, to obtain the hardness profile through the thickness, and correlate it with the damage dose profile. Following this, the dispersed barrier hardening (DBH) model is implemented to calculate the hardness of each layer of the irradiated material, based on the displacement damage and He concentration from simulations. Next, a simplified analytical model for the measured hardness at different depths is developed with the assumption that the plastic zone under the indenter is hemispherical and the hardness measured at any given depth depends on the average hardness of the plastic zone volume. This analytical model is implemented with the help of a program written in MATLAB. The calculated hardness profile is compared with the experimental profile, and it is found to be in reasonably good agreement for different energies of the irradiating He ions. This model can be used not only for ion‐irradiated materials with varying doses in different layers but also for other metallic materials with surface layers having diffuse interfaces. Abstract : The surface of the ion‐irradiated material is treated as a multilayered structure with varying radiation dose, resulting in changing number density of displacement damage features and He bubbles. The oblique cross section nanoindentation hardness is modeled as an average of the hardness of individual layers inside the plastic zone. The hardness–depth profile thus obtained agrees well with experimental results.